Songs and storytelling – a therapeutic theatre-making process as a tool to heal the wounds of the past - Mkhoma, Themba (My University, 2017)
The main intention of this paper is to share my experiences and discoveries explored through a theatre-making qualitative research process. In this manner, I created and directed my own autobiographical play as a means of revisiting and working through specific traumatic events in my past. The aim is to share how this helped heal the wounds of the past. In this paper, I have included my personal encounters, my observations and my reflections how Therapeutic Theatre and theatre-making methodologies were used in creating, in rehearsing and in the performance of the play to facilitate the healing of my traumatic past. The play, entitled Home Is Where Pap En Vleis Is, deals with a specific event believed to be the source of the trauma I have been dealing with. I used the play as a vehicle to journey into a dark forest to face my demons. As in Psychodrama, or in Robert Landy’s Role Method, the actor who played me took an auxiliary role while I, as the director, took the role of the helper. Together, we journeyed into the dark forest of my psyche to meet the ghosts needing to be laid to rest. Apart from seeking healing, as a training Drama Therapist, I also wanted to learn about the transformative potential of Therapeutic Theatre. As in the mythological Gilgamesh’s quest (Booker 2004:72) or as in the hero’s journey (Campbell 1968: 227), I wanted to come back with the boon. I needed to collect the “valuable prize”, by contributing to the development of Therapeutic Theatre in the South African context. Sharing the play with the audience was also a way of journeying with the larger community.
A research report submitted to the Faculty of Humanities University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Arts (Drama Therapy), 2017
Keywords: Drama--Therapeutic use; Play--Psychological aspects; Humanistic psychotherapy